Khashâis al-Mâ’ fî Al-Qur’an Al-Karîm - Sujiat Zubaidi Shaleh; Sitti Zafirah Tilsaf (Universitas Darussalam Gontor, 2020)
The beginning of the creation of life on earth, starting with the creation of living things created from water, there is no life on this earth that does not need water. Many studies discussed water but water was discussed only from a scientific point of view. Whereas in the Qur'an, there are many “kauniyah verses” which are indirectly related to one of the phenomena of the universe about water. By using descriptive methodology analysis, the researcher tries to examine the characteristics of water in the Qur'an by using a scientific approach to understand the intent of the “kauniyah verses” in the Qur'an. The result of this study is the first, the Qur'an states that Allah created water for the first time in this universe before creating the heavens and the earth. With all his will and power, Allah created His throne made of water which is above the seventh sky without any pillars below it. The Second, with the water, Allah the Almighty creates everything that is on earth to become a life such human , animals, plants and other living things. Furthermore, the purpose of the meaning of water is a blessing, mercy, pleasure, an essential and greatest gift bestowed by Allah SWT on all His creatures, especially for humans. The Third, with water, it can also be used as a means of treatment for a disease, especially if the water is recited from the holy verses of the Qur'an so that the molecules in the water will turn into beautiful crystal-shaped molecules. It was because that the water is a chemical compound and also has a water molecular structure, the existence of a negative pole on O (oxygen) and a positive pole on H (hydrogen) causes water molecules to be polar. According to its chemical formula ordinary molecules are written with H2O.